Increased Azithromycin Susceptibility of Multidrug-Resistant Gram-Negative Bacteria on RPMI-1640 Agar Assessed by Disk Diffusion Testing - Milton Meerwein; Andrea Tarnutzer; Michelle Böni; Françoise Van Bambeke; Michael Hombach; Annelies S. Zinkernagel (MDPI AG, 2020)
Increasing antibiotic resistances and a lack of new antibiotics render the treatment of Gram-negative bacterial infections increasingly difficult. Therefore, additional approaches are being investigated. Macrolides are not routinely used against Gram-negative bacteria due to lack of evidence of in vitro effectiveness. However, it has been shown that Pseudomonas spp. are susceptible to macrolides in liquid RPMI-1640 and clinical data suggest improvement in patients' outcomes. So far, these findings have been hardly applicable to the clinical setting due to lack of routine low-complexity antimicrobial susceptibility testing (AST) for macrolides. We therefore optimized and compared broth microdilution and disk diffusion AST. Multidrug-resistant Gram-negative bacteria (Escherichia coli, Enterobacter cloacae, Klebsiella pneumoniae, Pseudomonas aeruginosa) were tested for azithromycin susceptibility by disk diffusion and broth microdilution in Mueller-Hinton and RPMI-1640 media. Azithromycin susceptibility of Enterobacteriaceae and a subgroup of P. aeruginosa increased significantly on RPMI-1640 agar compared to Mueller-Hinton agar. Further, a significant correlation (Kendall, τ, p) of zone diameters and minimal inhibitory concentrations (MICs) was found on RPMI-1640 agar for E. coli (−0.4279, 0.0051), E. cloacae (−0.3783, 0.0237) and P. aeruginosa (−0.6477, <0.0001). Performing routine disk diffusion AST on RPMI-1640 agar may lead to the identification of additional therapeutic possibilities for multidrug-resistant bacterial infections in the routine clinical diagnostic setting.